Feminicidio and #NiUna Menos: An Analysis of Twitter Conversations During the First 3 Years of the Argentinean Movement. (June 2021) - Belotti, Francesca; Comunello, Francesca; Corradi, Consuelo
This article analyzes the Twitter conversations carrying the hashtag #NiUnaMenos produced in Argentina during the time of the marches in 2015, 2016, and 2017, by adopting a quali-quantitative method. After describing the origins of NiUnaMenos, we illustrate the mobilizing force of femicide in a context of technopolitical use of social media by women's movements. Data analysis diachronically shows to what extent and in what terms conversations on NiUnaMenos refer to gender violence and femicide. The conclusions highlight the effective combination of femicide narrative, the Argentinean human rights tradition, and Twitter usages in transforming violence against women into a general civic matter.